The possible effect of light exposure reduction via eye patches after the examination for retinopathy in premature infants? An observational study in preterm neonates - Tunç, Gaffari; Yalınbaş Yeter, Duygu; Karagöz, Feyzanur; Tecer, Emine Erva; Akkan, Senem; Kılıçbay, Fatih (The European Research Journal, 2023)
Objectives: This study aimed to examine whether infants with and without eye patches differ in terms of vital signs and clinical status after retinopathy of prematurity examination. Methods: Premature infants hospitalized in study center between June 2021-April 2022 were included. Group 1 is consisted of infants whose eyes were not closed after retinopathy of prematurity examination. Those infants whose eyes were closed eye-patches consisted of group 2. Vital signs were followed for 24 hours following the examination. Demographic, medical and follow-up data were all recorded prospectively. Vital signs were evaluated in accordance with birth week and weight. Pain score was evaluated by Neonatal Pain, Agitation, and Sedation Scale. Results: Pain scores were found to be lower in group 2 (p < 0.020). Although the systolic blood pressure, diastolic blood pressure, and mean blood pressure values of group 2 were found to be lower than group 1, they were within normal limits (all p < 0.05). Vomiting was not observed at all in Group 1 (p = 0.036). There was no significant difference between the groups in terms of fever, respiratory rate, heart rate, SpO2, and blood glucose values. Conclusions: This study showed that using an eye patch in infants after an eye examination reduces pain and increases comfort of infants. Although their pain scores are lower, taking necessary precautions are recommended for these patients in terms of vomiting. Thus, eye patches can be suggested as a non-pharmacological pain-reducing method after get advanced stagnation by the support of more studies with a larger number of participants.